Penerapan Pembelajaran IPA Berbasis Etnosains melalui Kearifan Lokal untuk Meningkatkan Keterampilan Proses Sains dan Berpikir Kritis: Kajian Literatur - Marpaung, Dewi Natalia; Retnawati, Heri; Arianingrum, Retno (Faculty of Teacher Training and Education, Musamus University, 2024)
Science learning based on local wisdom is increasingly gaining attention in the context of learning, especially ethnoscience approach that connects science with traditional knowledge of the local wisdom. This study aims to make science learning more relevant and contextual for students by connecting scientific concepts with local wisdom in the community. The research method used literature review study by collecting reference sources from Google Scholar. Literature studies that examine various studies related to the application of science learning based on local wisdom to use local wisdom in science education in schools. The data analysis technique used in this literature study research is content analysis that contains science process skill and critical thinking skills. The journals that are in accordance with the topic consist of 10 articles. The results of this study indicate that the application of ethnoscience through local wisdom can improve students' understanding of scientific concepts, strengthen their involvement in the learning process, can improve students' science process skills, such as observing, experimenting, analysing, and concluding data, and encouraging the development of critical thinking skills.